2021
DOI: 10.1093/genetics/iyaa021
|View full text |Cite
|
Sign up to set email alerts
|

Pan cancer patterns of allelic imbalance from chromosomal alterations in 33 tumor types

Abstract: Somatic copy number alterations (SCNAs) serve as hallmarks of tumorigenesis and often result in deviations from one-to-one allelic ratios at heterozygous loci, leading to allelic imbalance (AI). The Cancer Genome Atlas (TCGA) reports SCNAs identified using a circular binary segmentation algorithm, providing segment mean copy number estimates from single-nucleotide polymorphism DNA microarray total intensities (log R ratio), but not allele-specific intensities (“B allele” frequencies) that inform of AI. Our app… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…To identify genomic regions that harbor SCNAs, we applied hapLOHseq. To assess the accuracy and potential of this approach, we compare SCNAs inferred from RNA-seq to high-confidence SCNA calls detected from DNA SNP microarray data, which have been documented previously ( Sivakumar et al , 2021 ) with an estimated false-positive rate <3% ( Vattathil and Scheet, 2016 ). For these purposes, since the RNA and DNA were derived from the same tissue (or tumor), we treat the SNP microarray results as a gold standard.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To identify genomic regions that harbor SCNAs, we applied hapLOHseq. To assess the accuracy and potential of this approach, we compare SCNAs inferred from RNA-seq to high-confidence SCNA calls detected from DNA SNP microarray data, which have been documented previously ( Sivakumar et al , 2021 ) with an estimated false-positive rate <3% ( Vattathil and Scheet, 2016 ). For these purposes, since the RNA and DNA were derived from the same tissue (or tumor), we treat the SNP microarray results as a gold standard.…”
Section: Resultsmentioning
confidence: 99%
“… Note : hapLOHseq and CaSpER performance evaluation. Rows 1–3 show performance results at the gene level obtained by comparing each method to the gold standard ( Sivakumar et al , 2021 ). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite epigenetic alterations like altered methylation pattern, as proposed for MEX3A in the context of breast cancer [ 58 ], genomic instability events come progressively in the focus of cancer biology, as chromosomal alterations are prominent in nearly all cancers and serve as the hallmark of cancer [ 59 , 60 ]. Analyses of somatic copy number alterations (SCNAs) revealed that roughly 94% harbor an allelic imbalance.…”
Section: A Snapshot View Of Mex3a’s Disease Driving Potential In Cancermentioning
confidence: 99%
“…Analyses of somatic copy number alterations (SCNAs) revealed that roughly 94% harbor an allelic imbalance. In this context, amplification of chromosome 1q was amongst recurrent events in 33 tumor types [ 60 ], including hepatocellular carcinoma with a frequency of 46–86% [ 61 ]. MEX3A is encoded on chromosome 1q22 within a region (1q21-1q25) that is gained in various cancers [ 62 , 63 , 64 ] and encodes several pro-oncogenic genes, e.g., RAB25 [ 65 ].…”
Section: A Snapshot View Of Mex3a’s Disease Driving Potential In Cancermentioning
confidence: 99%